Foamy Melamine Resin–Silica Aerogel Composite-Derived Thermal Insulation Coating - Dongfang Wang; Yabin Ma; Yingjie Ma; Baolei Liu; Dewen Sun; Qianping Ran (Nanomaterials)
A novel class of SiO2 aerogel-based resin composite with a self-formed foamy structure and an extremely low thermal conductivity, as well as excellent fire resistance, was fabricated via a room temperature and atmospheric pressure route. The self-formed foamy structure was achieved by utilizing SiO2 aerogel particles not only as a thermal insulative functional additive filler but also as nano-sized solid particles in a Picking emulsion system, adjusting the surface tension as a stabilizer at the interface between the two immiscible phases (liquid and air in this case). The results of foamy structure analyses via scanning electron microscopy, micro-CT, and N2 adsorption–desorption isotherms validate the successful generation of a micro-scale porous structure with the enhancement of the aerogel nano-scale solid particles at the wall as a stabilizer. A combination of multiscale pores imbues the aerogel-based foamy coating with a low thermal conductivity, as well as a high cohesive strength. For the foamy coating studied, with variable emulsion/foaming agent/aerogel ratios of 1/2/x, the thermal conductivity decreases from 0.141 to 0.031 W/m·K, and the cohesive strength increases from being non-detectable to 0.41 MPa. The temperature difference, which is a direct indicator of the thermal insulation behavior of the foamy coating, can increase from 12.1 °C to 48.6 °C under an 80 °C hot plate.